PENGARUH PUPUK KOMPOS MABAR DAN NPK YARA MILA 16:16:16 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) - Donatus Dahang; Lyndon Parulian Nainggolan; Muhammad Fauzan Zulazmi; Junius Firmanta Tarigan (Universitas Quality, 2023)
Research has been carried out using Mabar Compost and NPK Yara Mila 16:16;16 on lettuce (Lactuca Sativa L.). The aim of the study was to determine the effect of Mabar Compost Fertilizer, the effect of NPK Yara Mila 16:16:16, and the effect of the interaction between the two types of fertilizer on the growth and yield of lettuce plants. The study used a factorial randomized block design consisting of two factors. Factor I: Dosage of Mabar Compost with the symbol